2023
DOI: 10.3390/ijms24065700
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Pharmacokinetics, Disposition, and Duration of Action of the Tumour-Targeting Peptide CEND-1

Abstract: CEND-1 (iRGD) is a bifunctional cyclic peptide that can modulate the solid tumour microenvironment, enhancing the delivery and therapeutic index of co-administered anti-cancer agents. This study explored CEND-1’s pharmacokinetic (PK) properties pre-clinically and clinically, and assessed CEND-1 distribution, tumour selectivity and duration of action in pre-clinical tumour models. Its PK properties were assessed after intravenous infusion of CEND-1 at various doses in animals (mice, rats, dogs and monkeys) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… 21 It revealed favourable pharmacokinetics in humans and no signs of toxicity of iRGD as a monotherapy and in combination with nabpaclitaxel and gemcitabine and suggests that the use of iRGD led to an improved anti-tumour activity in these patients. 50 , 51 , 52 Further clinical trials in patients with pancreatic cancer and other tumour entities are underway to test whether iRGD can improve the efficacy of standard therapy in this and other tumour entities.…”
Section: Resultsmentioning
confidence: 99%
“… 21 It revealed favourable pharmacokinetics in humans and no signs of toxicity of iRGD as a monotherapy and in combination with nabpaclitaxel and gemcitabine and suggests that the use of iRGD led to an improved anti-tumour activity in these patients. 50 , 51 , 52 Further clinical trials in patients with pancreatic cancer and other tumour entities are underway to test whether iRGD can improve the efficacy of standard therapy in this and other tumour entities.…”
Section: Resultsmentioning
confidence: 99%
“…Kang et al invented a superparamagnetic iron oxide nanocage, which realized targeted gene therapy based on tumor-specific siRNA and was used to treat osteosarcoma in vivo [18]. Piiper's group demonstrated that a bifunctional cyclic peptide, CEND-1, shows high tumor selectivity and duration in preclinical tumor models of liver cancer and breast cancer in vivo [19], which may provide a tumor-specific delivery system for anticancer drugs. In another study, it was reported that a virus-free gene therapy system can specifically release genetic modifiers in solid tumors without affecting normal tissues in mice, representing an advanced system for applying gene therapy to cancer patients [20].…”
Section: Novel Therapeuticsmentioning
confidence: 99%